Internal Financial Determinants of Profitability: Evidence From Rural Banks in Indonesia - Arnanto, Tito Teguh; Lutfi, L. (Manunggal Halim Jaya, 2025)
Rural banks (BPR) in Indonesia face persistent challenges of low profitability, weak capital adequacy, and high credit risk, despite their vital role in financing micro and small enterprises. This study investigates how internal financial indicators—Capital Adequacy Ratio (CAR), Non-Performing Loans (NPL), Loan to Deposit Ratio (LDR), Cash Ratio (CR), and Operating Expenses to Operating Income (BOPO)—affect profitability, measured by Return on Assets (ROA), in rural banks under the OJK Jember jurisdiction during 2021–2023. Using purposive sampling, 33 rural banks were selected, and panel data regression with the Random Effects Model was applied following Chow, Hausman, and Breusch-Pagan LM tests. The results indicate that BOPO has a significant negative impact on ROA, highlighting operational efficiency as the primary determinant of profitability. By contrast, CAR, NPL, LDR, and CR exhibit no significant individual effects, although collectively they explain 88.03% of ROA variation. These findings confirm that efficiency drives profitability in small-scale financial institutions, while other financial ratios exert joint but indirect influence. This study contributes to the literature by clarifying the relative importance of efficiency in rural banking. It provides practical implications for managers and regulators to strengthen cost control, prudent lending, and liquidity management, thereby promoting sustainable performance.